Political Polarization and Traditional Folktales: Examining Conflicts in the Legend of Mirah-Golan - Supandi, Muhammad Diaz; Puspitasari, Niken Sylvia (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
The folktales of Mirah and Golan in Ponorogo, East Java, Indonesia, are deeply embedded with cultural and social values, reflecting political polarity closely linked to group conflicts and dynamics. This journal analyzes the political polarization depicted in these folktales by identifying the groups involved, their political ideologies, and the forms of conflict that emerge from these ideological divides. Using a qualitative approach and narrative analysis, the study explores the underlying meanings and messages within the tales of Mirah and Golan. The analysis reveals that these folktales illustrate conflicts and group dynamics resulting from divergent political perspectives. These narratives highlight the political polarization experienced by communities within the stories and echo similar phenomena observed in contemporary political landscapes. By examining these folktales, the research sheds light on how historical and cultural narratives can mirror and inform our understanding of current political issues, providing valuable insights into the nature of political conflicts and group interactions in historical and modern contexts.